2015
DOI: 10.5114/jcb.2015.50659
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric analysis and clinical outcomes in CT-based mould brachytherapy in early oral cancers in patients unfit for surgery

Abstract: PurposeBrachytherapy in the oral cavity is an important alternative to conventional treatment, and provides a high localized dose and short overall treatment time. A rapid fall of dose beyond radioactive source makes it possible for increased tumour control and sparing surrounding tissue, while short overall treatment duration reduces risk of tumour repopulation. Moulds are fabricated to hold the catheters in position as closely as possible to tumour surface to provide adequate dose coverage of tumour volume a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…External beam radiotherapy may be used to address this. However, in our patient, the tumor was small in size, was located superficially and there was no perineural invasion, so we felt comfortable using brachytherapy [7,8,[15][16][17][18][19]. The patient tolerated the procedure well with only grade two acute mucositis of the soft palate.…”
Section: Treatmentmentioning
confidence: 74%
See 1 more Smart Citation
“…External beam radiotherapy may be used to address this. However, in our patient, the tumor was small in size, was located superficially and there was no perineural invasion, so we felt comfortable using brachytherapy [7,8,[15][16][17][18][19]. The patient tolerated the procedure well with only grade two acute mucositis of the soft palate.…”
Section: Treatmentmentioning
confidence: 74%
“…The radiation dose to the normal tissues can be lowered by this method in select cases [15][16][17]. When tumors are technically accessible and superficially-located, surface mold brachytherapy technique may be utilized in oral and oropharyngeal cancers [7,8,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of using custom mould brachytherapy are also scarce. A few studies have used them for treatment of skin cancers and the results have been promising, compared to other modes of radiation delivery [13,15,22,23,24]. In a few studies, 3D planning based custom mould brachytherapy was used and they showed very good dose distribution with respect to PTV coverage and OAR sparing.…”
Section: Discussionmentioning
confidence: 99%
“…Brachytherapy has been widely employed as a salvage or definitive modality in recurrent and/or localized early lesions, respectively [ 1 ]. In recent years, with the evolution of new techniques, high-dose-rate brachytherapy (HDR-BT) is usually preferred as it is an outpatient-based procedure, which does not require hospitalization and reduces radiation safety concerns [ 2 , 3 ]. For sites within head and neck region like oral cavity and oropharynx, brachytherapy provides an effective alternative especially when surgery is morbid or not possible [ 4 ].…”
Section: Purposementioning
confidence: 99%
“…For sites within head and neck region like oral cavity and oropharynx, brachytherapy provides an effective alternative especially when surgery is morbid or not possible [ 4 ]. Effective inter-disciplinary approach helps in fabrication of customized radiation-carrier prosthesis, which enables accurate dose delivery with excellent dose distribution [ 2 ].…”
Section: Purposementioning
confidence: 99%